2015
DOI: 10.1007/s11095-015-1636-z
|View full text |Cite
|
Sign up to set email alerts
|

Human Monoclonal Antibody Fragments Targeting Matrilin-3 in Growth Plate Cartilage

Abstract: Yeast display successfully selected antibody fragments that are able to target cartilage tissue in vivo. Coupling these antibodies to chondrogenic endocrine and paracrine signaling molecules has the potential to open up new pharmacological approaches to treat childhood skeletal growth disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…We previously used yeast display to identify scFv antibody fragments with high affinity and specificity toward the cartilage-specific protein matrilin-3, and we showed that these antibody fragments can home to growth plate cartilage when administered in vivo. 3 In the current study, we created fusion proteins combining these antibody fragments with human IGF-1, and we showed that at least two of these fusion proteins (IGF1-c22 and -c26) retained both cartilage-binding ability and IGF-1 biological activity. Using an ex vivo metatarsal bone culture system, we found that these IGF-1 fusion proteins can stimulate whole-bone growth.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…We previously used yeast display to identify scFv antibody fragments with high affinity and specificity toward the cartilage-specific protein matrilin-3, and we showed that these antibody fragments can home to growth plate cartilage when administered in vivo. 3 In the current study, we created fusion proteins combining these antibody fragments with human IGF-1, and we showed that at least two of these fusion proteins (IGF1-c22 and -c26) retained both cartilage-binding ability and IGF-1 biological activity. Using an ex vivo metatarsal bone culture system, we found that these IGF-1 fusion proteins can stimulate whole-bone growth.…”
Section: Discussionmentioning
confidence: 74%
“…We previously identified three clones of cartilage-targeting singlechain variable (scFv) antibody fragments (c13, c22, and c26). 3 In the current study, we used these cartilage-targeting scFvs to generate fusion proteins of cartilage-targeting IGF-1 (hereafter referred to as IGF1-c13, IGF1-c22, and IGF1-c26; Figure 1A), and we tested their potential to deliver IGF-1 to the growth plate cartilage. To this end, we first used ELISA to assess the ability of our fusion proteins to bind to matrilin-3 (both human and mouse).…”
Section: Igf-1 Fusion Proteins Retained Cartilage-binding Abilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Wile-type SPIN1, wild-type SPIN4, or SPIN4 mutant were cloned into pSecTag plasmid containing a secretary peptide sequence so that the expressed proteins are secreted into the culture media. An antibody Fc region was inserted at the carboxyl terminus, connected with a G4S linker (37) to allow protein purification using protein A resin as previously described (38). Briefly, Protein A resin (GenScript, Piscataway, NJ) slurry (1-5 ml) was packed into a glass Econo-column (Bio-RAD), and equilibrated with 50 ml of binding/ washing buffer (0.15 M NaCl, 20 mM Na2HPO4, pH 8.0).…”
Section: Purification Of Fc-tagged Spin4 Proteinsmentioning
confidence: 99%